2021
DOI: 10.7717/peerj.10736
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic cues to individuality in wild male adult African savannah elephants (Loxodonta africana)

Abstract: The ability to recognize conspecifics plays a pivotal role in animal communication systems. It is especially important for establishing and maintaining associations among individuals of social, long-lived species, such as elephants. While research on female elephant sociality and communication is prevalent, until recently male elephants have been considered far less social than females. This resulted in a dearth of information about their communication and recognition abilities. With new knowledge about the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 47 publications
7
16
0
Order By: Relevance
“…Vocal space differentiation could also reflect a personal signature, which could depend on the particulars of the event, like the composition of the group, the role or rank of individuals within it, etc. In an interesting study on social rumbles of wild mature male L. Africana [49], the authors showcased that elephants produced unique vocalizations facilitating individual recognition. They identified 5 spectral features that contributed almost evenly to these personalized variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vocal space differentiation could also reflect a personal signature, which could depend on the particulars of the event, like the composition of the group, the role or rank of individuals within it, etc. In an interesting study on social rumbles of wild mature male L. Africana [49], the authors showcased that elephants produced unique vocalizations facilitating individual recognition. They identified 5 spectral features that contributed almost evenly to these personalized variations.…”
Section: Discussionmentioning
confidence: 99%
“…The study of elephant vocalizations, in a variety of settings and contexts, has been focused predominantly on female individuals and families, while less attention has been given to male elephant groups, as males appeared significantly less active vocally. Targeted studies on male elephants however, are illuminating a yet undiscovered aspect of their vocal repertoire [48][49][50]. Our current study also focuses on male African elephant vocalizations -rumbles in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found significant differences in rumble characteristics amongst individuals, supporting previous findings using similar methodologies (Stoeger & Baotic 2016;Wierucka et al 2021). Our frequency 5% was extremely similar to Wierucka et al (2021) and also fit within the range of the fundamental frequency previously reported (Baotic & Stoeger 2017;Poole et al 1988;Stoeger & Baotic 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Beyond localization, this near real-time monitoring approach could be expanded to categorizing sources, thus locating particular animals or behaviours of interest, such as detecting alarm rumbles in elephants. It has been suggested that rumbles contain information on the individual animal and its emotional state [ 1 , 2 , 54 ]. Localization and classification approaches could, therefore, be used to monitor individual elephants, or entire herds, and their welfare across a spatially constrained area using dense arrays.…”
Section: Discussionmentioning
confidence: 99%